2018
DOI: 10.1111/anu.12846
|View full text |Cite
|
Sign up to set email alerts
|

Validation of processed animal proteins (mono-PAPS) in experimental diets for juvenile gilthead sea bream (Sparus aurataL.) as primary fish meal replacers within a European perspective

Abstract: Experimental diets were formulated to evaluate a "pure" poultry meat meal (PMM) source in diets formulated for juvenile gilthead sea bream (Sparus aurata L.). The digestible protein contribution of fish meal in a control diet was substituted by 25%, 50% and 75% of a processed poultry meat meal (PMM) on a digestible crude protein (DCP) basis and by 5% and 10% for an enzyme-treated feather meal (EFM) and also a spray-dried haemaglobin meal (SDHM), respectively. In a consecutive trial, diets were designed to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 43 publications
0
22
0
1
Order By: Relevance
“…Whole‐body composition was not apparently affected by the dietary treatments, although due to analytical problems whole‐body fat content could not be analysed. Previous studies showed that fat content was higher in gilthead seabream fed diets containing blood meal and feather meal (Nogueira et al, ), while it was not significantly affected when fish were fed diets containing feather meal, spray‐dried haemoglobin or poultry meal alone (Davies et al, ; Karapanagiotidis et al, ). Additionally, hepatosomatic and viscerosomatic indexes have been reported to be significantly higher in fish fed insect meal‐based diets (Gasco et al, ; Sánchez‐Muros et al, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Whole‐body composition was not apparently affected by the dietary treatments, although due to analytical problems whole‐body fat content could not be analysed. Previous studies showed that fat content was higher in gilthead seabream fed diets containing blood meal and feather meal (Nogueira et al, ), while it was not significantly affected when fish were fed diets containing feather meal, spray‐dried haemoglobin or poultry meal alone (Davies et al, ; Karapanagiotidis et al, ). Additionally, hepatosomatic and viscerosomatic indexes have been reported to be significantly higher in fish fed insect meal‐based diets (Gasco et al, ; Sánchez‐Muros et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed that gilthead seabream was able to cope with dietary fishmeal replacement by rendered animal proteins. Recent studies in this fish species recommend the dietary replacement of up to 50% of fishmeal with poultry meal (Davies et al, 2019;Karapanagiotidis et al, 2019) and inclusion of feather meal at 50 to 100 g/kg and blood meal at 100 g/kg (Davies et al, 2019;Nogueira, Cordeiro, Andrade, & Aires, 2012). Protein digestibility was lower in diets containing feather meal than in those containing poultry meal or spray-dried haemoglobin meal for several carnivorous fish species, including gilthead seabream (Davies, Gouveia, Laporte, Woodgate, & Nates, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Even with higher intake, these diets presented lower cost per unit of biomass produced when compared to the others, probably due to the utilization of meat and bone meal, which is a lower cost ingredient. Other studies have shown that the costs of fish production can be reduced by replacing, to the maximum extent possible, the use of high value protein sources such as fishmeal, with alternative energy sources and low-cost protein (Cerdeira et al, 2018;Davies et al, 2019;Diógenes et al, 2019). The inclusion of protein and energy levels above the T-37 diet contributed to the gradual increase in feeding cost without providing a significant increase in biomass, which is undesirable in both productive and environmental aspects (El Sayed et al, 2015;Salze and Davis, 2015).…”
Section: /8 Discussionmentioning
confidence: 99%
“…In intensive systems, fish are frequently subject to high levels of stress and are susceptible to many adverse events, which can lead to physiological changes (Tu et al, 2015;Zhang et al, 2017). Fish nutrition experiments with purified ingredients are not effective in verifying the interaction between diet components and processing, so they are usually validated in research using practical diets (Rawles et al, 2018;Davies et al, 2019). On-farm experiments using practical diets may have greater applicability due to their similarity to production reality (Kabir et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, commercial and/or wild stock of M. rosenbergii has been sharply declining all around the globe during the last two decades. Therefore priorities must be directed toward an approach to identify optimum stocks in a given culture condition (Bowyer et al, ; Davies, Gouveia, Laporte, Woodgate, & El‐Haroun, ; El‐Husseiny, Hassan, El‐Haroun, & Suloma, ; Goda et al, , ; Hassan et al, ; Hassaan, Mahmoud, et al, ; Hassaan, Soltan, et al, ; Kumar et al, ; Sagar et al, ). The growth performance of prawns is influenced by various factors such as water, soil quality, stocking density, sex ratio, feeding methods, and feed types.…”
Section: Introductionmentioning
confidence: 99%